Potential for winter wheat production in western Canada: A CERES model winterkill risk assessment - Savdie, I.; Whitewood, R.; Raddatz, R. L.; Fowler, D. B. (Canadian Journal of Plant Science, 1991)
The introduction of a practical winter wheat (Triticum aestivum L.) production system, which utilizes direct no-till seeding into standing stubble immediately after harvest of the previous crop (stubbling-in) and snow trapping, has reduced the risk of winterkill and permitted expansion of the North American crop northeastward to include most of western Canada's agricultural area. The large expanse of this region results in considerable variation in climatic conditions and associated risks of winterkill. In the present study, 29 yr of climatic data for 53 stations were analyzed utilizing the CERES winterkill algorithm with the objective of determining the spatial distribution of various winterkill levels for stubbled-in "Norstar" winter wheat in western Canada. These simulations indicated that insulating snow cover is the pivotal climatic factor in winter wheat survival in the arid and transitional grassland ecoregions. The reliability of early winter snow cover appears to be more critical than the total overwinter amount. In the more northerly boreal climatic ecoregion, the limiting factor may be poor acclimation conditions and/or early incursion of killing Arctic air. This study demonstrates the usefulness of crop models, such as CERES, in extending the results of site-specific field studies to new areas and in risk analysis for planning and decision making. Key words: Winter wheat, winterkill, CERES model, Western Canada